2023
DOI: 10.1002/slct.202204410
|View full text |Cite
|
Sign up to set email alerts
|

Graphene‐Oxide‐Coated, Polypyrrole‐Supported, Nano Zerovalent Iron Nanocomposites for Adsorption of Hexavalent Chromium from Wastewater

Abstract: The hexavalent chromium in water is extremely toxic to most living organisms and can cause many diseases. In this work, we developed Polypyrrole (PPy), Polypyrrole/graphene oxide (PPy/ GO) nanocomposite, and Polypyrrole/graphene oxide/zerovalent iron nanoparticles (PPy/GO/n-ZVI) nanocomposite for adsorption of Cr (VI) from water. PPy/GO nanocomposite showed the highest Cr (VI) removal capacity for 10 % (weight) loading of GO. PPy/GO/n-ZVI nanocomposite showed the highest Cr (VI) adsorption capacity for 50 % ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
(126 reference statements)
0
0
0
Order By: Relevance
“…During this period, the active sites were occupied by Cr (VI) ions, and the removal rate slowed down. The fitted result in Figure 6b indicated that reactions at both the Cr(VI) concentration levels followed the quasi-second-order kinetic equation, with an R 2 of 0.999, which was similar to Waghmare's study with polypyrrole/GO-modified ZVI nanoparticles [49]. In contrast, a similar Cr(VI) removal study using GO/rGO-base composite materials without ZVI followed the pseudo-first-order reaction [26].…”
Section: Kinetic Analysissupporting
confidence: 77%
“…During this period, the active sites were occupied by Cr (VI) ions, and the removal rate slowed down. The fitted result in Figure 6b indicated that reactions at both the Cr(VI) concentration levels followed the quasi-second-order kinetic equation, with an R 2 of 0.999, which was similar to Waghmare's study with polypyrrole/GO-modified ZVI nanoparticles [49]. In contrast, a similar Cr(VI) removal study using GO/rGO-base composite materials without ZVI followed the pseudo-first-order reaction [26].…”
Section: Kinetic Analysissupporting
confidence: 77%